Payments by modelled results: A novel design for agri-environmental schemes. (March 2021) - Bartkowski, Bartosz; Droste, Nils; Ließ, Mareike; Sidemo-Holm, William; Weller, Ulrich; Brady, Mark V.
Highlights: Result-based agri-environmental payments are costly to implement and imply payment uncertainty for farmers. We propose agri-environmental payments by modelled results (PAMR) as solution. PAMR unite advantages of conventional action-based and result-based payments. PAMR could address trade-offs among multiple objectives and management for long-term effects. Abstract: From a theoretical point of view, result-based agri-environmental payments are clearly preferable to action-based payments. However, they suffer from two major practical disadvantages: costs of measuring the results and payment uncertainty for the participating farmers. In this paper, we propose an alternative design to overcome these two disadvantages by means of modelling (instead of measuring) the results. We describe the concept of agri-environmental payments by modelled results (PAMR), including a hypothetical example of payments for the protection and enhancement of soil functions. We offer a comprehensive discussion of the relative advantages and disadvantages of PAMR, showing that it not only unites most of the different advantages of result-based and action-based schemes, but also adds two new advantages: the potential to address trade-offs among multiple policy objectives and management for long-term environmental effects. We argue that PAMR would be a valuable addition to the agri-environmental policy toolbox in the EU and beyond, while also reflecting recent advancements in agri-environmental modelling.